Assistance in Compiling Cash Flow Reports for Small Businesses in Kerinjing Village - Tjandrakirana, Rina; Ermadiani, Ermadiani; Budiman, Anton Indra (Sricommerce: Journal of Sriwijaya Community Services, 2022)
Cash flow statement is an important report for every company. Cash flow is described as cash inflows and cash outflows. Cash flow statements are often used to describe the company's ability to meet operating costs and company obligations, so that in order to generate additional profits, the company must have cash to reinvest. Broadly speaking, the cash flow statement consists of three activities, namely operational activities, investing activities and financing activities. Each of these activities has its own role in the cash flow statement. The focus of problems faced by small businesses in general is not making bookkeeping, so they do not prepare financial reports including cash flow statements. This will cause the business process to falter and even go bankrupt. In addition, bookkeeping can be useful for knowing the company's financial condition, avoiding fraud, and can also help in making decisions.This Community Service will be carried out in Kerinjing village. This activity will be carried out by providing technical guidance to small business actors, where small business actors will be given prior knowledge of accounting science, the importance of accounting in a business, as well as financial reports, especially cash flow reports. Then they will also be given technical guidance on how to prepare a cash flow statement, and will be given assistance in preparing a cash flow statement for their business.